Interest Rates in Savings Groups: Thrift or Threat? - le Polain, Maïté; Sterck, Olivier; Nyssens, Marthe (World development, 2018)
•Interest rates in savings groups aim at (1) encouraging capital accumulation, (2) allocating capital efficiently and (3) remunerating savings.•We identify three gaps between these objectives and SG members' perceptions and practices.•Gap 1: SG members turn their savings into loans to avoid the risks of storing cash rather than to achieve rapid capital accumulation.•Gap 2: Credit allocation is not guided by expected credit performance but rather by concerns of fairness and risk diversification.•Gap 3: SG members consider that the accumulated interest belongs to the group and should reward active borrowers rather than passive savers. Savings group (SG) models are praised for achieving financial inclusion for the poorest at a very low cost. Promoted by international NGOs, SG models are inspired by indigenous savings and credit associations (ROSCAs). SG models however differ in that they prescribe lending the pooled savings to group members for an interest. The interest rate aims to (1) boost capital accumulation, (2) allocate scarce capital efficiently, and (3) remunerate and incentivize savers. This paper builds on a six-month fieldwork conducted in DR Congo consisting of direct observations of SG meetings and interviews with SG participants and practitioners. We study the gaps between SG practitioners’ objectives and SG participants’ perceptions and practices related to the interest rate. Our research pays particular attention to the local context and local norms that interfere with SG practitioners’ objectives. Our analysis highlights three gaps. First, SG participants turn savings into credit for security purposes rather for rapid capital accumulation. Second, credit allocation decisions are guided by fairness and security concerns rather than efficiency. Third, SG participants often regard the accumulated interest as belonging to the group and to active borrowers rather than to passive savers. Our results invite development actors to pay greater attention to the potential risks of the SG approach for its participants. Despite the common appellation “savings groups”, this microfinance innovation builds upon credit and strongly encourages its members to go into debt.